2005
DOI: 10.1007/s11910-005-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Migraine headache: Options for acute treatment

Abstract: The optimal acute treatment of migraine requires recognition of the multitude of migraine presentations, the frequency of total attacks, and number of days of headache disability. These initial diagnostic steps are initiated in the waiting room, but phase-specific and stratified treatment selection requires having mutual understanding, trust, and belief through extensive discussion. The imperative acute treatment goal must be to treat early, but not too often, a fact represented by a 75% or better occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The early treatment of migraine is therefore a race against central sensitization (13,14) and, in support of this, data from a pivotal open-label study have indicated that triptan therapy may be more efficacious if initiated before the onset of cutaneous allodynia (10). In this study, 53 migraineurs treated their pain either early (1 h after pain onset) or late (4 h after pain onset) on in the attack, with the presence or absence of cutaneous allodynia recorded at the time of treatment.…”
Section: Evolution Of Migraine Painmentioning
confidence: 99%
“…The early treatment of migraine is therefore a race against central sensitization (13,14) and, in support of this, data from a pivotal open-label study have indicated that triptan therapy may be more efficacious if initiated before the onset of cutaneous allodynia (10). In this study, 53 migraineurs treated their pain either early (1 h after pain onset) or late (4 h after pain onset) on in the attack, with the presence or absence of cutaneous allodynia recorded at the time of treatment.…”
Section: Evolution Of Migraine Painmentioning
confidence: 99%
“…While a wide range of effective pharmacological and nonpharmacological therapies are available for treatment and prevention of headaches, 7,8 current treatment of chronic headache is frequently suboptimal 9‐14 …”
mentioning
confidence: 99%
“…For the practitioner prescribing nonspecific treatment, additional potentially important differences exist from migraine-specific therapy ( Table 2). 21 The Disabilities in Strategies of Care (DISC) treatment trial reports that significantly disabled migraine sufferers (MIDAS disability grades II, III, IV of IV) had better outcomes with triptans as initial acute treatment than those stepping through nonspecific treatments. 22 Although nonspecific treatments are low direct cost therapies for both consumer and insurance plans, the DISC trial also instructs that lower total costs are associated with migraine-specific triptan therapy.…”
Section: Selection Of the Appropriate Acute Management: Nonspecific Omentioning
confidence: 99%
“…Lastly, on occasion it appears that an individual may just not respond to a migraine-specific therapy warranting reassessment. 21 Multiple migraine presentations with varying symptoms, creates uncertainty. This variability necessitates versatility in migraine-specific formulations and at times co-mixing this treatment with another analgesic or symptomatic drug.…”
Section: Migraine-specific Selectionmentioning
confidence: 99%